2018
DOI: 10.1111/jth.14304
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of plasma von Willebrand factor levels in health and disease

Abstract: To cite this article: Swystun LL, Lillicrap D. Genetic regulation of plasma von Willebrand factor levels in health and disease. J Thromb Haemost 2018; 16: 2375-90. of genetic modifiers of plasma VWF levels may allow for better molecular diagnosis of type 1 VWD, and enable the identification of individuals at increased risk for thrombosis. Validation of trait-mapping studies with in vitro and in vivo methodologies has led to novel insights into the life cycle of VWF and the pathogenesis of quantitative VWF abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 129 publications
1
61
0
Order By: Relevance
“…It is estimated that variability at the VWF locus accounts for 5% VWF heritability, whereas that at the ABO blood group locus accounts for approximately 25% VWF heritability. 73 An interesting example of somatic mosaicism of VWF gene mutations has been described by Shen et al in a large family with type 2A VWD. The father carried a mutated VWF gene, p. Arg1597Trp, and transmitted this mutation to his nine offspring.…”
Section: Genotype Versus Phenotypementioning
confidence: 96%
See 1 more Smart Citation
“…It is estimated that variability at the VWF locus accounts for 5% VWF heritability, whereas that at the ABO blood group locus accounts for approximately 25% VWF heritability. 73 An interesting example of somatic mosaicism of VWF gene mutations has been described by Shen et al in a large family with type 2A VWD. The father carried a mutated VWF gene, p. Arg1597Trp, and transmitted this mutation to his nine offspring.…”
Section: Genotype Versus Phenotypementioning
confidence: 96%
“…Type 1 patient analysis in the Netherlands study demonstrated the association of STXBP5 with a VWF:Ag level reduction of -3 IU/dL per allele and of CLEC4M with a VWF: Ag level of -4.3 IU/dL and VWF activity of -5.75 IU/dL per allele. 31,73 Eleven additional quantitative trait loci were found to associate with plasma VWF levels: ARSA, C2CD4B, DAB2IP, FCHO2, GIMAP7, HLA-DGA1, OR13C5, PDHB, RAB5C, ST3GAL4, and TAB1/SYNGR1. 73 Sabater-Lleal et al identified 11 loci associated with VWF levels: PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPS-NAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This is supported by the observation of a strong association between VWF levels and the degree of loading of VWF with A and B antigens 10,11 . This would explain the robust association found between the ABO blood group and circulating concentrations of VWF 12 and factor VIII (FVIII) of which VWF is the transport protein. Individuals with A1 and B blood groups have on average 20% higher circulating VWF and FVIII levels than those with O or A2 13,14 groups, high plasma levels of VWF and FVIII being associated with increased VT risk [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other non-VWF and non-ABO genes have been implicated to influence VWF through multiple mechanisms including secretion, glycosylation, and clearance. However, a proportion of VWF variation remains unexplained [135][136][137].…”
mentioning
confidence: 99%